The reasons behind teachers’ reluctance on the use of the new methods and techniques of teaching maths according to the teacher gender (Journal of the College of Basic Education, 2022)
This research aims to find out the reasons for the reluctance of teachers and teachers on the use of modern methods and methods in teaching mathematics, the researcher adopted the descriptive analytical method that describes the phenomenon accurately, and to achieve the goal of the researcher prepared a questionnaire consisting of (30) paragraph distributed over five dimensions (obstacles related In school organization, obstacles related to the teacher, obstacles related to the curriculum, obstacles related to the learner (student), obstacles related to the nature of teaching methods). The researcher relied on the design of the tool on the pentagon of Likart, and to verify the authenticity of the tool, the researcher presented it to a group of arbitrators as the apparent honesty was adopted. The tool was applied to a survey sample consisting of (30) teachers and a time interval of 25 days. The Pearson correlation coefficient was calculated as showing the scores obtained by the respondents in the two responses and reached (0.90). This ratio is sufficient to check the stability of the tool and using the average score obtained by each paragraph of the tool. The results were as follows: The obstacles affecting the teacher were the most influential in the reluctance of the teachers of mathematics in the primary stage of the use of modern methods and methods in education, followed by the importance of the obstacles related to the organization of the school and then the obstacles related to the curriculum and then the obstacles related to the nature of teaching methods followed by the obstacles related to the learner (Pupil) Thus, all the paragraphs of the scale is one of the reasons that led to the reluctance of teachers to use modern methods and methods in teaching mathematics, each according to their field